PENGEMBANGAN SIKAP TOLERANSI SISWA SEKOLAH DASAR PADA KEBERAGAMAN DI INDONESIA - Mita Anggraeni; Sally Alya Febriyani; Yona Wahyuningsih; Tin Rustini (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2022)
Indonesia is a country that has a lot of diversity ranging from ethnic, cultural, and religious diversity. With so much diversity in Indonesia, tolerance has become a demand for everyone, including elementary school students, an attitude of tolerance that grows and develops in the family, community and school environment will avoid problems such as disputes and conflicts caused by existing diversity. An attitude of tolerance that grows and develops properly will produce harmony and harmony in the environment. This paper aims to describe the importance of developing tolerance attitudes of elementary school students to diversity in Indonesia through the role of parents, teachers and learning models in schools to develop tolerance attitudes of elementary school students to diversity in Indonesia. The analytical method used in this article is a literature study. With the diversity in Indonesia, the development of an attitude of tolerance for elementary school students is very much needed